PERTUMBUHAN DAN HASIL JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA KOMPOSISI MEDIA TANAM SERBUK GERGAJI, AMPAS TEBU DAN JANTUNG PISANG YANG BERBEDA - Hanifah, Evy (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2025)
White oyster mushroom is one of the edible and wood mushrooms widely consumed by the community because it contains high protein, vitamins, minerals, amino acids, low carbohydrates, fat, and calories. The composition of sugarcane bagasse is 47% carbon, 6.5% hydrogen, 44% oxygen, 2.5% ash, 2.5% crude protein, 43–52% crude fiber, 84.2% NDF, 51% ADF, 33.2% hemicellulose, 40.3% cellulose, 11.2% lignin, energy value 50%, and banana hearts contain 12.051% protein; 34.831% carbohydrates; 13.050% fat; phosphorus; calcium; iron; vitamin A; vitamin B1; and vitamin C. The aim of this study was to determine the growth and yield of white oyster mushrooms on different substrate compositions of sawdust, sugarcane bagasse, and banana hearts. This study was an experimental study using a completely randomized design (CRD) with a single factor consisting of 5 treatments: E1 (960 g sawdust, without sugarcane bagasse and banana hearts), E1 (930 g sawdust, 15 g sugarcane bagasse and 15 g banana hearts), E2 (935 g sawdust, 15 g sugarcane bagasse and 10 g banana hearts), E3 (920 g sawdust, 25 g sugarcane bagasse and 15 g banana hearts), and E4 (925 g sawdust, 25 g sugarcane bagasse and 10 g banana hearts), each treatment with 3 replications. Data analysis was performed using One Way ANOVA with a significance level of 0.05. The results showed that the substrate composition of 920 g sawdust, 25 g sugarcane bagasse, and 15 g banana hearts (E3) had a significant effect on the mycelial growth of white oyster mushrooms (25.33 days), the number of fruiting bodies of white oyster mushrooms (23.33 fruits in the first harvest and 9.00 fruits in the second harvest), and the fresh weight of fruiting bodies of white oyster mushrooms (110.00 g in the first harvest and 83.33 g in the second harvest) as the best performance.